Stock Price Prediction Using Datamining With Novel Computing Approach - et. al., R. Suganya, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Foreseeing financial exchange is consistently a difficult work. As an ever increasing number of individuals are associated with exchanging , its consistently an idealistic conduct to predict about the future price. By means of predicting the future stock price, experts and analysts in the stock field can buy or sell accordingly. In order to predict the stock value, financial specialists utilized crucial examination, specialized investigation and innovative investigation. Different strategies, for example, utilizing stock pointers additionally end up being a value a few. Yet, even though there are many techniques available the result of stock prediction is always a random one because of it adhoc nature. The experts in this field can also track the various information channel in order to increase their predicting performance. The previous work consolidates more on the result rather than the methods used. In this paper, we proposed a novel technique which uses the technological methods with that of the technical views and the changing news information’s about the stock. We implemented fuzzy rational algorithm with that of the hybrid neural network in conjunction with the k nearest matching points. The optimization techniques used here are the combination of the soft computing methods.